Anselm Strauss - Werk, Aktualitat und Potentiale Mehr als Grounded Theory. - CARSTEN DETKA; HEIKE OHLBRECHT; SANDRA TIEFEL (VERLAG BARBARA BUDRICH, 2021)
The American sociologist Anselm Strauss is one of the most influential scientists in the field of qualitative social research - there is no qualitatively oriented researcher who is not familiar with Strauss' Grounded Theory. The theoretical work of Anselm Strauss has also become extremely important. This volume discusses Strauss's work in its relevance to contemporary social research.